RETRACTED: Analysis of the parameters of technological material sprinkling devices of special road vehicles (ꞷδ=const): MAN CLA 18.280 4x2 BB CS45 - Turdibekov Saloxiddin; Isoxanov Utkir; Shermatov Shamshir; Abdusamatov Erkinjon (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001